2018
DOI: 10.1080/23294515.2018.1550123
|View full text |Cite
|
Sign up to set email alerts
|

Genes wide open: Data sharing and the social gradient of genomic privacy

Abstract: This study reports on 13 semistructured in-depth interviews to qualitatively explore the experiences of individuals who publicly shared their direct-to-consumer genetic testing results on the platform openSNP. In particular, we focused on interviewees' understanding of privacy. Participants reported that the likelihood and the magnitude of privacy harms depend on gender, ethnicity, sexual orientation, the stigma associated with certain clinical conditions, the existence of adequate legislation, and the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…The implementation of the General Data Protection Regulation (GDPR) engenders a greater awareness of the value of data, issues of ownership and privacy and highlights potential risks to participants [43]. Haeusermann et al [26] explored the reasons why individuals shared their own personal health data online. They found that participants who were openly sharing their own data continued to have concerns about privacy, and that the motivation for sharing despite this risk was that it could lead to new developments.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the General Data Protection Regulation (GDPR) engenders a greater awareness of the value of data, issues of ownership and privacy and highlights potential risks to participants [43]. Haeusermann et al [26] explored the reasons why individuals shared their own personal health data online. They found that participants who were openly sharing their own data continued to have concerns about privacy, and that the motivation for sharing despite this risk was that it could lead to new developments.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, social groups having more to fear in terms of discrimination may be discouraged from participating. This would create a socio-economic gradient on access to medically relevant information, therefore potentially increasing health inequalities (Hausermann et al, 2018). Analogously, voluntary disclosure may induce insurers to increase premiums for non-disclosers, thus putting less affluent people at a further disadvantage.…”
Section: Trustworthiness: To Encourage Research Participationmentioning
confidence: 99%
“…Consumer perceptions of genetic information privacy vary depending on how well DTC-GT consumers read and comprehend privacy policies and terms of use agreements [22]. The United States National Library of Medicine (US NLM) understands how this variation may exist and has provided formal recommendations to address it.…”
Section: Dtc-gt Consumer Comprehension Of Terms Of Use Agreements mentioning
confidence: 99%
“…Critchley et al discovered, among the consumer concerns they identified, that the least trusted aspects of DTC-GT companies related to matters of consumer privacy. Adding to this finding is that of Haeusermann et al, who found that some DTC-GT consumers perceived privacy is an “illusion” [22]. This perception was based on the notion that electronic genetic information files can be easily hacked [22].…”
Section: Consumer Concerns and Perceptions About Dtc-gt Informatiomentioning
confidence: 99%
See 1 more Smart Citation